Risk for excessive anticoagulation during hemodialysis is associated with type of vascular access and bedside coagulation testing: Results of a cross-sectional study - De Troyer, Marijke; Wissing, Karl Martin; De Clerck, Dieter; Cambier, Marie-Laure; Robberechts, Tom; Tonnelier, Annelies; François, Karlien (Frontiers in Medicine, 2022)
Background Recommendations and practice patterns for heparin dosing during hemodialysis show substantial heterogeneity and are scantly supported by evidence. This study assessed the variability in unfractionated heparin (UFH) dosing during hemodialysis and its clinical and biological anticoagulatory effects, and identified explanatory factors of heparin dosing. Methods Cross-sectional study assessing UFH dosing, coagulation tests - activated partial thromboplastin time (aPTT) and activated clotting time (ACT) before dialysis start, 1h after start and at treatment end (4h) - and measurement of residual blood compartment volume of used dialyzers. Results 101 patients, 58% male, with a median dialysis vintage of 33(6-71) months received hemodialysis using a total UFH dose of 93064079 (range 3000-23050) IU/session. Use of a dialysis catheter (n=56, 55%) was associated with a 1.4 times higher UFH dose (p<0.001) irrespective of prior access function. aPTT increased significantly more than ACT both 1h and 4h after dialysis start, independent of the dialysis access used. 53% of patients with catheter access and ACT ratio <1.5 one hour after dialysis start had simultaneous aPTT ratios >2.5. Similar findings were present at 1 hour for patients with AVF/AVG and at dialysis end for catheter use. No clinically significant clotting of the extracorporeal circuit was noted during the studied sessions. Dialyzer’s blood compartment volume was reduced with a median of 9% (6-20%) without significant effect of UFH dose, aPTT or ACT measurements and vascular access type. UFH dose, aPTT, ACT and catheter use were not associated with spKt/Vurea either. Conclusions UFH dose adaptations based on ACT measurements frequently result in excessive anticoagulation according to aPTT results. Higher doses of UFH are used in patients with hemodialysis catheters without evidence that this reduces dialyzer clotting or improves urea clearance.